Development Of 3-dimensionally Printed Denture Base Material Utilizing Hybrid Polymer: A Preliminary Investigation - Nur A’fifah Husna Zahar; Durratul Aqwa Mohd Farid; Muhammad Syafiq Alauddin; Zulfahmi Said; Mohd Ifwat Mohd Ghazali; Hao-Ern Lee; Syazwani Mohamad Zol (Elsevier, 2024)
Indexed by WOS/Scopus/ERA